The effect of GeO2 and In2O3 doping on the dielectric properties of CaCu3Ti4O12 Ceramics prepared via vibro-milling method - Makcharoen W. (2014)
In this work, effects of GeO2 and In2O3 doping on the dielectric properties of CCTO were investigated. Doping levels range from 0.5 to 2.0 mol%. The vibro-milling method was employed for processing. The dopant addition produced a slightly smaller grain size. A reduction in dielectric constant was observed, but it is still high. The 2.0 mol% GeO2 and In2O3 doped samples exhibited high dielectric constant of about 25,000 and 23,000 and low dielectric loss with 0.06 and 0.05 respectively at room temperature and at 10 kHz. The dielectric measurements showed that the modified samples exhibited a strong dielectric independency of temperature and frequency. In addition, the loss tangent reduced after doping. From this results, it can be incurred that GeO2 and In2O3 doping, processed via vibro-mill are the suitable methods to achieve the stability of high εr and low loss ceramics. Copyright © Taylor &Francis Group, LLC.